Implementing a food safety program HACCP in the workplace - Pederick, Ben; Collins, Cath; Boland, Michael; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2006)
This program focuses on a large food service workplace and follows their food safety practices from the start to the end of the day. Interspersed with the visual footage are practical examples of employees following good hygiene practices, checking foods, cleaning, recording information and corrective action
DVD format
Keywords: Food -- Safety measures; Hazard Analysis and Critical Control Point (Food safety system); Food handling